Assessment of selected lecture chairs from University of the Philippines Diliman based on the design preferences of left-handed college students - Balbuena, Jennylyn A.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
In a classroom, left-handed individuals are experiencing difficulties in adopting tools and equipment intended for right-handed individuals. This descriptive study aimed to determine whether the existing designs of selected lecture chairs from different classrooms in the University of the Philippines Diliman cater to left handed college students. The researcher made use of a multi-method approach which involved a survey and a focus group discussion. Purposive sampling was used in selecting the five (5) lecture chairs. The chairs were evaluated based on their material, color, form or shape and size of the chair. Snowball sampling was used in identifying the six (6) respondents for the study. Findings showed that aesthetics and tactile sensation of the chairs contribute to the respondent's perceptions on comfort. In addition, it is concluded that the specific needs of left-handed students were not considered in the existing designs of the lecture chairs due to unfavorable orientation of the tablet arm. It was also found that ergonomics was not considered in the designs of the selected lecture chairs on account of the pain and discomfort experienced by the respondents. The study suggested to consider both aesthetics and functionality in order to produce an effective design for all the users.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Chair design -- Philippines